Facile synthesis of 3D MnNi-layered double hydroxides (LDH)/graphene composites from directly graphites for pseudocapacitor and their electrochemical analysis - Lee, Ilbok; Jeong, Gyoung Hwa; An, Soyeon; Kim, Sang Wook; Yoon, Songhun (Applied Surface Science, 2018)
Herein, MnNi-layered double hydroxides (LDH) were imbibed within the interlayers of graphene nanosheets. The anionic surfactant, sodium dodecyl sulfate played a role of graphite exfoliator adding interaction with metal cations. Using this process, layered MnNi-LDH-graphene nanocomposite was prepared without formation of graphene oxide. When applied into pseudocapacitor electrode, LDH-graphene with optimal ratio between Mn and Ni exhibited very stable cycle with 90% at 1400 cycles and high energy 47.29 Wh kg −1 at the power density of 7473 W kg −1 , which was attributed to highly stable layered LDH structure within conductive graphene layers.
Keywords: Electrochemical analysis; Facile synthesis; Graphene layers; Graphene nanocomposites; Graphene nanosheets; Highly stables; Layered double hydroxides; Power densities; Electrochemistry; Graphene; Graphite; Layered double hydroxides; Nanostructures; Supercapacitor